Electrochemically Controlled Deposition of Ultrathin Polymer Electrolyte on Complex Microbattery Electrode Architectures. Issue 3 (30th January 2019) - Abdelhamid, Muhammad E.; Rüther, Thomas; Veder, Jean-Pierre; Rodopoulos, Theo; Bhatt, Anand I.; Lee, Junqiao; Hollenkamp, Anthony F.; Horne, Mike D.; Huynh, Thuy; Ong, Andojo; Putman, Kate J.; Rowe, Genna; et al.
Abstract : Solid state microbatteries are highly sought after for emerging microsensor technologies. To overcome the problem of the dwarfing capacity resulting from the miniaturization of the battery, 3D-structured platform consisting of high surface area micropillar-shaped electrodes are used. However, applying a conformal and continuous solid polymer electrolyte films onto the intricate 3D electrodes is a crucial step toward achieving functional microbatteries. In this work, we present our approach for the development of polyethylene oxide (PEO)-acrylate based ion conducting polymer thin films which function as solid polymer electrolyte (SPE) and a separator. The SPEs were electrochemically deposited on the 3D electrodes resulting in ultrathin, continuous, conformal, and pinhole-free polymer films. The electrochemical and Li + ions transport properties of the SPEs were characterized by EIS measurements and cyclic voltammetry. Furthermore, the homogenous composition of the SPEs at various depths were confirmed by XPS depth profiling techniques.